Analisa Kandungan Formaldehid Pada Sediaan Cat Kuku (Kutek) yang Diperjualbelikan di Pasar Kota Wonogiri - Andriastuti, Deitra Aprilia; Nasikin, M. Ali; Rakhmayanti, Regia Desty (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
Nail polish is a pigment that is deposited in a volatile solvent to cover the natural color of the nail and as an attractiveness enhancer that uses formaldehyde. Formaldehyde (H2CO) with the trade name formalin solution, which functions as a nail polish hardener, so that the nail polish is more adhesive and thicker. This study aims to determine whether nail polish preparations traded in the Wonogiri city market contain formaldehyde with levels that exceed the limit according to the Regulation of the Head of the Food and Drug Supervisory Agency of the Republic of Indonesia Number 18 of 2015, which is <5%. Qualitative analysis used resorcinol reagent, while quantitative analysis used UV-Vis spectrophotometry at a wavelength of 550 nm. The sample used in this study was nail polish taken from the market in Wonogiri, 9 samples with sample codes A, B, C, D, E, F, G, H, and I. The results showed that 9 samples of nail polish studied meet the requirements of the level limit of less than 5%, with the largest level obtained at 3.349% for the code I sample and the smallest level at 0.750% for the code E sample. Keywords: nail polish, formaldehyde, UV-Vis spectrophotometry